Utilization of Durian Seed Flour in Making High Energy and Protein Cupcakes - Ima Saphira; Andi Eka Yunianto; Eliza Eliza (Universitas Pendidikan Indonesia, 2021)
Chronic energy deficiency is the cause of an imbalance between energy intake and expenditure. Efforts that can be made to overcome SEZ are by providing energy-rich foods. There must be innovative foods given to SEZ youth, such as cupcakes that use durian seed flour substitution. This study aims to determine the best formulation and acceptability and utilization of durian seed flour in the manufacture of high energy and protein cupcakes through proximate and fiber analysis. This research was conducted in March 2021. This study used an experimental research method with a non-factorial completely randomized design (CRD). The results of this study produced the selected cupcake, namely F2 with the formulation (75 g wheat flour and 75 g durian seed flour) and produced 328.92 kcal of energy (Per 100 g) of protein 12.23%, fat 12.60%, and carbohydrates 41, 65%. Further research is needed on the effect of giving durian seed flour cupcakes to KEK adolescents.